Use of near-infrared spectroscopy for determining the characterization metal ion in aqueous solution - Alfian Putra; Hesti Meilina; Roumina Tsenkova (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
This study uses Aquaphotomics to measure Cadmium (Cd) and Magnesium (Mg) in aqueous solutions by analysing the changes in water spectra that occur due to water-metal interaction. Metals have no absorbance in the NIR spectral range, thus the methods developed so far have focused on detection of metal-organic complexes. Measurements were performed with Cd (II) and Mg(II) in 0.1 M HNO3, in the 680-1090 nm (water second and third overtones) and 1110-1800 nm (water first overtone) spectral regions, and were subjected to partial least-square regression analysis. Metal ions were scanned by NIRSystem 6500 using cuvette cell with 2 mm path length, in three consecutive days. Data for two days were used as data set and the rest of the data were used as prediction set. The calibration and prediction statistics obtained in this study indicated the potential of NIRS to predict metal ions in aqueous 0.1 M HNO3 solution with correlation coefficient (R2pred.0.7). The RPD (residual predictive deviation) or ratio of standard error of prediction to the standard deviation, values were greater than 2, indicating that the model is appropriate for practical use (Cozzolino,2007). By using water matrix coordinates (WAMACS) from regression coefficient, obtained a consistency specific wavelength for each　metal.. These results showed that the PLS model were able to detect character metal ions in the NIR region of electromagnetic spectra with high accuracy even at very low concentrations (0-10 ppm).